First report of leaf blight disease caused by Aspergillus welwitschiae on Persicaria lapathifolia var. salicifolia in China - Shen, Zhihan (Plant disease, 2024)
Persicaria lapathifolia var. salicifolia (Sibth.) Miyabe, has long been extensively utilized in traditional medicine for its significant medical values (Seimandi et al, 2021). Despite its extensive use, the leaf blight disease of this plant has never been documented in China. However, in September 2023, the symptoms of leaf blight disease were observed on P. lapathifolia var. salicifolia on the campus of Zhejiang Normal University (29°8'3″ N, 119°37'47″ E), Zhejiang province, China. The disease incidence was 40% on the 50 plants surveyed, according to the field survey. The progression of leaf pathogenesis is mainly divided into three stages. Early symptoms manifested as the light yellow spots on the edges or tips of the leaves, which subsequently developed into brown or yellow irregular lesions and eventually led to the curling and wilting leaves. Thus, the leaf tissues (5 × 5 mm) from the border of diseased and healthy areas were surface-sterilized in 1% sodium hypochlorite for 3 min, followed by 75% ethanol for 30 s, and rinsed three times with sterile water. After drying on sterile filter paper, the leaf tissues were put on PDA medium and cultured at 25°C for 3 days. Seven purified fungal isolates were obtained, and one representative strain was selected for further identification. After that, the isolate was identified by the combination of morphological studies and molecular analysis. The fungi exhibited rapid growth on PDA, attaining a diameter of 80 to 85 mm in 5 days. The colonies were black with a yellow margin, and the reverse sides were light yellow and partly colorless. Moreover, the conidia were brown to black, smooth to slightly rough, measuring 3.2 to 3.8 μm (n = 30) in diameter, with radiated conidial heads and expanded ampulliform phialides under the optical microscope. Therefore, the isolate's characteristics were consistent with the descriptions of Aspergillus welwitschiae (Bres.) Henn. (Gherbawy et al, 2021). To further identify the isolate, the internal transcribed spacer (ITS) region (Gardeset al, 1993) and the second largest RNA polymerase subunit (RPB2) (Liu et al, 1999) were employed for phylogenetic analysis. The obtained sequences were despot in GenBank (Acc. Nos. OR797058 for ITS, OR797058 for RPB2, respectively), and exhibited a high degree of sequence homology to A. welwitschiae (MK450815, MK450818, LC179911, and LC000572), with 99% to 100% identity. Besides, multilocus phylogenetic analysis showed that the isolate gathered into one clade with A. welwitschiae. Based on the integrated morphological and molecular results, the isolate was determined to be A. welwitschiae. Six healthy 1-year-old P. lapathifolia var. salicifolia were used to verify Koch's postulates. Three leaves were wounded with sterile pins and inoculated with the conidial suspension (107 conidia/mL) of isolates, while plants inoculated with sterile water were used as controls. After sealing with plastic wrap for 24 hours, the plants were cultivated at 25 °C and 85% relative humidity. Necrotic lesions were observed on leaves 10 days after inoculation, while the control leaves remained asymptomatic. The fungi were re-isolated from the diseased leaves and identified as the original ones through morphological and molecular identification, confirming Koch's postulates. While A. welwitschiae has been reported to cause the rot disease of Sisal Bole in Brazil (Duarte et al, 2018) and maize ear in Serbia (Nikolic et al., 2023), to our knowledge, this study marks the first report of A. welwitschiae causing leaf blight on P. lapathifolia var. salicifolia in China, extending the host range to A. welwitschiae